2002
DOI: 10.1007/s10350-004-6257-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inulin Supplementation on Inflammation of Pouch Mucosa in Patients With an Ileal Pouch-Anal Anastomosis

Abstract: Enteral inulin supplementation leads to a decrease of inflammation-associated factors and to a reduction of inflammation of pouch mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(159 citation statements)
references
References 34 publications
0
144
2
4
Order By: Relevance
“…This study showed a significant reduction of the fecal inflammatory marker calprotectin in prebiotic-treated patients after 1 week compared to the placebo group, suggesting that these prebiotics were able to reduce chronic intestinal inflammation. 85 Welters et al 86 performed a crossover study in 24 patients with chronic pouchitis after colectomy for UC. The patients were given 24 g daily of inulin or placebo for 3 weeks.…”
Section: Prebiotics In Human Ibd Prebioticsmentioning
confidence: 99%
“…This study showed a significant reduction of the fecal inflammatory marker calprotectin in prebiotic-treated patients after 1 week compared to the placebo group, suggesting that these prebiotics were able to reduce chronic intestinal inflammation. 85 Welters et al 86 performed a crossover study in 24 patients with chronic pouchitis after colectomy for UC. The patients were given 24 g daily of inulin or placebo for 3 weeks.…”
Section: Prebiotics In Human Ibd Prebioticsmentioning
confidence: 99%
“…The prebiotic inulin and a combination of the probiotic organisms Lctb acidophilus La-5, Lctb delbruckii subsp. bulgaricus, Bfdbm Bb-12, and Streptococcus thermophilus significantly reduced inflammation [64]. The effect was enhanced by combination with metronidazole, suggesting a synergistic effect of the combination of anti-and probiotics in the treatment of experimental colitis [65].…”
Section: Iva-probiotic Effect In Animal Experimental Ibd Modelsmentioning
confidence: 90%
“…43 Similarly, germinated barley foodstuffs, including Ispaghula husk, have been shown to have some effect on mild to moderate IBD, whereas inulin supplementation leads to increased butyrate and lower levels of Bacteroides fragilis and Bacteroidetes in the feces of patients with chronic pouchitis. 44 Moreover, studies in migrant populations suggest individuals who move from Southeast Asia to western countries have a higher risk of developing IBD; this effect is likely secondary to changes in dietary habits and resultant effects on gut microbiota in genetically susceptible individuals. 45 .…”
Section: Gut Microbiota In Inflammatory Bowel Diseasementioning
confidence: 99%